Fatigue crack growth at the representative zones in friction stir welding of a heat-treatable aluminum alloy at 200oC - Tra, Tran Hung (Vietnam Journal of Science and Technology, 2018)
Aluminum alloy 6063-T5 plates were joined by friction stir welding technique. The fatigue crack growth (FCG) in the thermo-mechanical affected zone (TMAZ) and in the heat affected zone (HAZ) of the welding was examined at 200oC. Although the grain microstructure of the TMAZ was significantly refined in comparison with that of BM, the FCG rate in TMAZ and base metal was shifted a comparable amount when the test temperature was elevated from room temperature to 200oC. In the metallurgical view, the FCG rate in the fine grain TMAZ was higher than that in coarse grain HAZ and base metal site